2018
DOI: 10.3390/f9040192
|View full text |Cite
|
Sign up to set email alerts
|

Can Land Management Buffer Impacts of Climate Changes and Altered Fire Regimes on Ecosystems of the Southwestern United States?

Abstract: Climate changes and associated shifts in ecosystems and fire regimes present enormous challenges for the management of landscapes in the Southwestern US. A central question is whether management strategies can maintain or promote desired ecological conditions under projected future climates. We modeled wildfire and forest responses to climate changes and management activities using two ecosystem process models: FireBGCv2, simulated for the Jemez Mountains, New Mexico, and LANDIS-II, simulated for the Kaibab Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 119 publications
(160 reference statements)
2
43
0
Order By: Relevance
“…S12), implying that, despite restoration efforts, biomass loss is still possible. We found similar vegetation type changes as Loehman et al (2018) in a similar time frame but Flatley and Ful e (2016) found that vegetation type changes are possible further into the future.…”
Section: A) Live Pools Carbonsupporting
confidence: 66%
See 3 more Smart Citations
“…S12), implying that, despite restoration efforts, biomass loss is still possible. We found similar vegetation type changes as Loehman et al (2018) in a similar time frame but Flatley and Ful e (2016) found that vegetation type changes are possible further into the future.…”
Section: A) Live Pools Carbonsupporting
confidence: 66%
“…Still other studies found that, despite restoration efforts, extreme climate change conditions could result in significant biomass losses and deforestation (Taranc on et al 2014, Flatley and Ful e 2016, Loehman et al 2018. We also saw decreases in TEC and aboveground biomass in the no-harvest and status quo scenarios implying that without restoration there is a strong likelihood that forest biomass will decline with climate change due to high severity fires and low productivity.…”
Section: A) Live Pools Carbonmentioning
confidence: 47%
See 2 more Smart Citations
“…However, future warming increases uncertainty about maintaining these habitats even if uncharacteristically severe fires can be curtailed (Loehman et al . ).…”
Section: Spotted Owlsmentioning
confidence: 97%